Interactions of reading and semantics along the ventral visual processing stream. Issue 1 (2nd January 2019) - Neudorf, Josh; Ekstrand, Chelsea; Kress, Shaylyn; Neufeldt, Alexandra; Borowsky, Ron
ABSTRACT: Converging evidence supports a distributed-plus-hub view of semantic processing, in which there are distributed modular semantic sub-systems (e.g., for shape, colour, and action) connected to an amodal semantic hub. Furthermore, object semantic processing of colour and shape, and lexical reading and identification, are processed mainly along the ventral stream, while action semantic processing occurs mainly along the dorsal stream. In Experiment 1, participants read a prime word that required imagining either the object or action referent, and then named a lexical word target. In Experiments 2 and 3, participants performed a lexical decision task (LDT) with the same targets as in Experiment 1, in the presence of foils that were legal nonwords (NW; Experiment 2) or pseudohomophones (PH; Experiment 3). Semantic priming was similar in effect size regardless of prime type for naming, but was greater for object primes than action primes for the LDT with PH foils, suggesting a shared-stream advantage when the task demands focus on orthographic lexical processing. These experiments extend the distributed-plus-hub model, and provide a novel paradigm for further research.